Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Answer:
(x, y) = (-38/5, -38/5)
Step-by-step explanation:
6y - 9x = 24
-3y + 2x = 7 $\Rightarrow$ -6y + 4x = 14.
Adding the two equtions together, we get:
(6y - 9x) + (-6y + 4x) = 24 + 14.
Simplifying, we get:
-9x + 4x = 38
-5x = 38
x = -38/5.
So, 6y - 9 * (-38/5) = 24
y = -37/5
Answer:
Step-by-step explanation:
6y - 9x = 24
-6y + 6x = 21
-3x = 45
x = -15
-3y - 30 = 7
-3y = 37
y = -37/3
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.